Les premiers monastères d’Auvergne à la lumière de la documentation textuelle et archéologique (ve-xe siècle) : état de la question - Damien Martinez (Bulletin du Centre d’Études Médiévales d’Auxerre)
The Auvergne territory offers a wealth of archival sources for the early medieval period, which allows us to perceive the vitality of monasteries within the former diocese of Clermont. By studying both the original texts, and the archaeological data available, we can today have a better understanding of the conditions in which early monasteries were established in this region. The picture that emerges is somewhat sketchy, given the lack of archaeological data. The first observation we can make is that we had here a primitive type of monasticism, flourishing within an urban context, and encouraged by the local bishops, while other monastic institutions struggled to survive outside this urban setting. Then towards the end of the Carolingian period, this monasticism, though more dispersed throughout the Auvergne area, became more strongly anchored, both in the territory and in time, under the impetus of the local aristocracy.